Women's Participation in Decision-making Processes in Arctic Fisheries Resource Management - Sloan, Lindis (Forlaget Nora, Kvinneuniversitetet i Nord, Website: http://www.kun.nl.no/, 2002)
KUN (Kvinneuniversitetet i Nord), Centre for Knowledge and Equality: http://www.kun.nl.no/ With fisheries in the Arctic as the area of research, the intent of this project was to do research on three levels of resource management. • Individual power – ownership and leadership in fisheries and fishery-related businesses, • Structural or institutional power – influence in the systems and bodies that determine quota regulations and • Discursive power – the symbols, public images, assumptions and stereotypes that serve to uphold fisheries as a “male” domain. These are treated comparatively in an international study, involving subprojects in Canada, Greenland, Iceland, Norway and Sweden and one initiated by the Norwegian Sámi Parliament. The Faroe Islands have been included in the comparative part, but not in a separate project due to the timeframe. The studies and the resulting project report include comparative background descriptions of the fisheries and the gender equality situation for each country, and an overview of important decision-making bodies in fisheries management at different levels in the Arctic. Sustainable Development Working Group, Arctic Council